2016
DOI: 10.1097/jsm.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Randomized Controlled Trial

Abstract: This research showed that tendon fenestration is an alternative cost-effective treatment for recalcitrant PT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…All the articles included in the present review involved 326 individuals, most of whom were athletes practicing various sports and aged between 18 and 55 years. Functionality with VISA-p was assessed in eight studies [ 8 , 21 , 23 , 34 38 ], and pain was evaluated using a numeric scale in all studies except one [ 38 ]. The main features of these studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the articles included in the present review involved 326 individuals, most of whom were athletes practicing various sports and aged between 18 and 55 years. Functionality with VISA-p was assessed in eight studies [ 8 , 21 , 23 , 34 38 ], and pain was evaluated using a numeric scale in all studies except one [ 38 ]. The main features of these studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that there are no differences between the groups neither in the short nor in the long term. Along these lines, Resteghini et al [ 38 ] compared the effectiveness of AB versus saline and found no differences between groups. Finally, this review is in line with a previous study [ 21 ] that reported that PRP was not superior to placebo or DN at a 6-month follow-up for tendinopathy treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations